One-year recovery from breast cancer: Importance of tumor and treatment-related factors, resilience, and sociodemographic factors for health-related quality of life - Veličković, Katarina; Borrebaeck, Carl A. K.; Bendahl, Pär-Ola; Hegardt, Cecilia; Johnsson, Per; Richter, Corinna; Rydén, Lisa; Hallberg, Ingalill Rahm (Frontiers in Oncology, 2022)
Aim: The study investigated the changes in health-related quality of life from diagnosis to one year after diagnosis in breast cancer patients, and the influence of clinical, psychological, and socio-demographic variables. An additional aim was to explore the mediating and moderating effect of resilience on changes in health-related quality of life. Methods: A longitudinal population-based study was conducted in southern Sweden. Newly diagnosed BC patients filled in measures of health-related quality of life, resilience, and socio-demographic variables at diagnosis (N = 980) and one-year post-diagnosis (N = 780). Clinical variables were extracted from the Swedish national breast cancer quality registry. Mixed model analyses were performed. Results: Most health-related quality of life outcomes declined from diagnosis to one-year post-diagnosis. Role limitations due to emotional problems remained the same, whereas mental health improved. Lower health-related quality of life outcomes were associated with symptomatic detection and axillary dissection. Patients with a higher TNM stage and histologic grade, ER negative and HER2 positive status, who received chemotherapy, antibody therapy, or bisphosphonate therapy, had a steeper decline in outcomes. Changes in resilience were positively associated with all outcomes but did not mediate or moderate changes in any. Resilience at baseline moderated changes in bodily pain, vitality, and mental health, higher baseline resilience being associated with a steeper decline, possibly due to floor or ceiling effects. Patients with lower socio-economic status, educational level, and older age had lower health-related quality of life. Conclusion: Physical health-related quality of life among breast cancer patients declined one-year post-diagnosis, whereas mental health-related quality of life improved. Low resilient patients may be especially vulnerable at diagnosis. Biopsychosocial assessment at diagnosis can help identify patients who may require additional support. A multidimensional treatment plan should be started early to help overcome the problems in everyday activities.